Negotiating boundaries and borders qualitative methodology and development research - Smith, Matt, Dr (Studies in qualitative methodology ;, 2007)
As international development presents enormous moral, political and ethical challenges, so researching and understanding it requires negotiation of its contested contours. The chapters draw on research conducted around the world using a range of methodologies, perspectives and commitments, rooted in diverse disciplines. Through their exploration of the interrelationship of qualitative methodologies and development theory, policy and practice, the book demonstrates the importance of placing qualitative methodologies within their conceptual, practical and political contexts. It also highlights the important but contested contribution that qualitative methodology can make to not only understanding development, but engendering it. This book explores qualitative methodology and development in terms of the ways researchers negotiate boundaries and borders. It asks questions of development research, critiques relationships between researchers and subjects, and challenges connections between research and change. It demonstrates the importance of placing qualitative methods within their right context. This book series is available electronically online.